Iconic Fictional Object as Separately Copyrighted Work from the Original Work - Dian Ayu Muthoharoh (Jurnal Media Hukum, 2021)
Copyright is one of the IPR branches that protect the human’s intellectual work in the field of science, arts, and literature. The film is a creation that is protected by copyright. In a film, there are not only characters that are easy to remember but also specific properties uniquely used by the characters, especially the main character. This property is called an iconic fictional object. This normative juridical legal research will discuss one legal issue, whether an iconic fictional object can be separately protected from the original work. Based on the analysis in this study, an iconic-fictional object is not explicitly stated as work protected by copyright according to Article 40 of Copyright Law No. 28 of 2014. However, iconic fictional objects fulfil elements of a work entitled to copyright protection: The creative work in the fields of science, art, and literature; Created by the ability, skill or expertise of the creator; and Expressed in real form. Furthermore, The United States Court of Appeals for the Ninth Circuit on DC Comics vs Mark Towle Batmobile case had argued that iconic fictional objects could be separately protected from the original work as long as they meet three conditions: (1) Physical as well as conceptual qualities, (2) Sufficiently delineated, and (3) Especially distinctive and contain some unique elements of expression.